Analysis of Independence, Effectiveness, and Efficiency Ratio as Measure of Financial Performance of the Lampung Province Government 2019–2023 - Anggi Jumiafitri Waldani; Puja Rizqy Ramadhan; Vina Arnita (Utan Kayu Publishing, 2025)
This study aims to assess the financial performance of the Lampung Provincial Government through the ratios of independence, effectiveness, and efficiency from 2019 to 2023. The research is descriptive with a quantitative approach and data collected through documentation. The analyzed data are secondary data. The results show that the average fiscal independence ratio remains low despite an increase in the last two years. The effectiveness of Local Own-Source Revenue (PAD) collection is considered quite good and consistently effective; however, in the final year, there was a decline, making it less effective.